2015
DOI: 10.1007/s13277-015-3970-5
|View full text |Cite
|
Sign up to set email alerts
|

Loss of protocadherin-17 (PCDH-17) promotes metastasis and invasion through hyperactivation of EGFR/MEK/ERK signaling pathway in hepatocellular carcinoma

Abstract: Metastasis has been one of the major reasons for cancer-related mortality, with multiple genes and pathways being involved in this complex process. Given the molecular variations underlying metastasis of hepatocellular carcinoma (HCC) remains largely unknown; in our previous work, we found copying number of protocadherin-17 (PCDH-17) was significantly deleted in HCC tissues that occurred to metastasize compared with that in the primary HCC without metastasis. Therefore, we hypothesized that PCDH-17 may suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…2C). CD9/MRP-1 is closely linked to plateled derived growth factor mediated glioma cell migration (21), downregulation of MGST1 weakens cell adhesion in PC12 cells (22) whereas PCDh17 regulates actin dynamics and inhibits migration and invasion (23,24). In contrast, many pro-migratory genes like ADAMTS4, MGAT4A, SPP1, STC1 and SNAI2/SLUG are downregulated by sCPE (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2C). CD9/MRP-1 is closely linked to plateled derived growth factor mediated glioma cell migration (21), downregulation of MGST1 weakens cell adhesion in PC12 cells (22) whereas PCDh17 regulates actin dynamics and inhibits migration and invasion (23,24). In contrast, many pro-migratory genes like ADAMTS4, MGAT4A, SPP1, STC1 and SNAI2/SLUG are downregulated by sCPE (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of homophilic cell-adhesion proteins, termed protocadherins, is associated with tissue development and growth (7). The epigenetic inactivation of genes that code for protocadherins is associated with the development and growth of several malignant tumor types (8,9). The protocadherin GA12 (PCDHGA12) gene, one of the genes coding for protocadherin, is located on chromosome 5 (10).…”
Section: Introductionmentioning
confidence: 99%
“…Protocadherin 17 (PCDH-17), also known as PCH68 and PCDH68, belongs to the protocadherin gene family, a subfamily of the cadherin superfamily [19], which is located at human chromosome 13q21.2 [20]. Increasing evidences have revealed the dysregulation of PCDH-17 was involved in multiple tumors, including bladder cancer, colorectal adenocarcinoma, hepatocellular carcinoma and gastric cancer [20][21][22][23]. Notably, Giefing et al found PCDH-17 acted as a tumor suppressor gene in LSCC [24].…”
mentioning
confidence: 99%